2020
DOI: 10.18203/2394-6040.ijcmph20204760
|View full text |Cite
|
Sign up to set email alerts
|

A study on stigma and apprehensions related to COVID-19 among healthcare professionals in Delhi

Abstract: Background: Public health emergencies during pandemics of communicable diseases, may cause fear leading to social isolation and stigma. Cases have been reported of healthcare professionals (HCPs), facing discrimination on account of heightened fear and misinformation. However, there is dearth of literature with regards to the nature and magnitude of this stigma. Hence, this study was conducted to assess perceived and experienced stigma related to the Coronavirus disease 2019 (COVID-19) among HCPs and also asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 11 publications
1
42
1
Order By: Relevance
“…Our findings showed no stigmatization on the part of the PHCWs. This is contrary to other studies in Nigeria and abroad which revealed that healthcare workers were highly stigmatized by people around them [13][14][15][16][17][18]. The possible explanation for this could be that the people believed that these are PHCWs who are not frontline workers who are in direct contact with the COVID-19 patients.…”
Section: Discussioncontrasting
confidence: 66%
“…Our findings showed no stigmatization on the part of the PHCWs. This is contrary to other studies in Nigeria and abroad which revealed that healthcare workers were highly stigmatized by people around them [13][14][15][16][17][18]. The possible explanation for this could be that the people believed that these are PHCWs who are not frontline workers who are in direct contact with the COVID-19 patients.…”
Section: Discussioncontrasting
confidence: 66%
“…In one study, 69.5% of HCWs reported rude and threatening behaviours against them by the public, while 30% reported receiving derogatory remarks (Yadav et al . 2020). Such displays of discriminatory behaviour from the public against nurses may be due to nurses’ high level of involvement in the management and care of suspected and/or infected patients, which puts them at higher risk of contracting the virus compared to other community members (Dye et al .…”
Section: Discussionmentioning
confidence: 99%
“…Research that quantitatively examined the extent of COVID-19 stigma among HCWs is limited. Studies from Nigeria [11], Pakistan [12], and India [13] reported that 28.3%, 41.9%, and 70% of studied HCWs experienced some form of stigma, respectively. However, these and other studies assessed COVID-19 stigma with non-specific/non-validated tools or among quarantined HCWs or non-HCWs [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%